Intention as a mediator in the interrelations of factors in health information-seeking behaviour on healthcare websites among youth - Clement George, Andrew Jason (2020)
The Internet has changed the way we search for information. Information is readily available to us with the push of a button, and it is undeniable that health is an area of interest for Internet users, especially among youth. In recent years, extensive research has been carried out to study the relationship between Malaysian youth and their perceptions of reproductive health; ranging from knowledge and awareness levels to lifestyle choices. However, minimal research has been done to study youth e-health literacy levels on the subject matter, therefore, the objective of this study is to examine the factors that influence youth behaviour towards using healthcare websites to search for reproductive health information. This study was guided by the Theory of Reasoned Action (TRA) which suggests that the best indicator of behaviour is intention, and that intention is formed by a person’s attitude towards performing a specific behaviour, along with the social pressure (from peers, family, schoolmates, and/or colleagues) to perform said behaviour. Participants for the study were 400 youth (from 18 – 40 years of age) based in the Klang Valley area. Data was collected through survey questionnaires that consisted of 47 close-ended and open-ended questions. The research instrument used in this study included the framework of the TRA namely: Attitude, Subjective Norms, Intention and Behaviour. Data collected was analysed using the IBM SPSS Statistics 22.0 software where regression analyses were carried out to understand the predictive nature of the variables in the framework. Overall, the findings found that youth who have positive (favourable) attitudes and adequate social support/pressure towards using healthcare websites to find reproductive health information are likely to have a high intention to do so, which is a key indicator of the respondents actual behaviour to perform the act. One crucial finding in the context of this study is how subjective norms is a stronger predictor of intention compared to attitude. In conclusion, the study’s findings are in line with the TRA framework and past research findings. Ministries, NGOs and private institutions that advocate better sexual and reproductive health (SRH) practices in Malaysia should leverage on the influence of new media to improve health literacy levels among youth.